Male circumcision programmes in Kenya: lessons from the Kenya AIDS Indicator Survey 2007 - Zebedee Mwandi; Rebecca Bunnell; Peter Cherutich; Jonathan Mermin; Andrea A Kim; Anthony Gichangi; Patrick Mureithi; Timothy A Kellogg; Tom Oluoch; James Muttunga; Carol Ngare; Evelyn Kim; et al.
OBJECTIVE: To provide guidance for male circumcision programmes in Kenya by estimating the population of uncircumcised men and investigating the association between circumcision and infection with the human immunodeficiency virus (HIV), with particular reference to uncircumcised, HIV-uninfected men. METHODS: Data on men aged 15 to 64 years were derived from the 2007 Kenya AIDS Indicator Survey, which involved interviews and blood collection to test for HIV and herpes simplex virus 2 (HSV-2). The prevalence of HIV infection and circumcision in Kenyan provinces was calculated and the demographic characteristics and sexual behaviour of circumcised and uncircumcised, HIV-infected and HIV-uninfected men were recorded. FINDINGS: The national prevalence of HIV infection in uncircumcised men was 13.2% (95% confidence interval, CI: 10.8-15.7) compared with 3.9% (95% CI: 3.3-4.5) among circumcised men. Nyanza province had the largest estimated number of uncircumcised, HIV-uninfected men (i.e. 601 709), followed by Rift Valley, Nairobi and Western Province, respectively, and most belonged to the Luo ethnic tribe. Of these men, 77.8% did not know their HIV status and 33.2% were HSV-2-positive. In addition, 65.3% had had unprotected sex with a partner of discordant or unknown HIV status in the past 12 months and only 14.7% consistently used condoms with their most recent partner. However, only 21.8% of the uncircumcised, HIV-uninfected men aged 15 to 19 years were sexually active. CONCLUSION: The Kenyan male circumcision strategy should focus on the provinces with the highest number of uncircumcised, HIV-uninfected men and target young men before or shortly after sexual debut.